2023
DOI: 10.3389/fpubh.2022.1040012
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 breakthrough infections during the second wave of COVID-19 at Pune, India

Abstract: Breakthrough infections following SARS-CoV-2 vaccination remain the global concern. The current study was conducted during the second wave of COVID-19 (1st March−7th July 2021) in Pune, India, at two tertiary care hospitals. Of the 6,159 patients diagnosed as COVID-19, 372/2,210 (16.8%) were breakthrough infections. Of these, 81.1 and 18.8% received one or two doses of Covishield or Covaxin, respectively. Of note, 30.7% patients were with comorbidities, hypertension being the commonest (12.44%). The majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
4
1
Order By: Relevance
“…BTI was reported in 18.5% (115/ 620) of positive COVID-19 respondents. This was similar to findings reported by Doke et al in Pune who studied HCWs after the second wave, where they reported BTIs of 16.8% [ 13 ]. Sharma et al reported symptomatic COVID-19 infections in 16.9% of HCWs and BTI in 13.3% [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…BTI was reported in 18.5% (115/ 620) of positive COVID-19 respondents. This was similar to findings reported by Doke et al in Pune who studied HCWs after the second wave, where they reported BTIs of 16.8% [ 13 ]. Sharma et al reported symptomatic COVID-19 infections in 16.9% of HCWs and BTI in 13.3% [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Three of the serious, hospitalized patients had diabetes mellitus as a preexisting co-morbid condition and no case fatalities were observed. In concurrence with our findings, symptoms for BTI were less severe with very few hospitalizations in the ICMR study conducted by Gupta et al, which reported only 67 cases (9.8%) of hospitalization and three (0.4%) case fatalities [ 21 ], while a multicentric study done in India by Rahi et al reported 8.57% (6/70) of hospitalization [ 23 ], and Doke et al in Pune recorded 23.36% (43/184) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, few cases of SARS-CoV-2 breakthrough infections were found at prevalence of 5.41% in this study. Similar to higher breakthrough infection rates were reported recently in India (5.6 and 16.8%) 35,36 . This finding was the first report of such data in Cameroon and support the fact that current COVID-19 vaccines, even though highly efficient to prevent severe clinical forms of the disease, do not prevent SARS-CoV-2 transmission 12,14 .…”
Section: Discussionsupporting
confidence: 90%
“…The risk among HCWs was high during the initial months of the pandemic (2)(3)(4). The pandemic is characterized by the rapid development of vaccines using conventional and new platforms, with immediate use to immunize the world population (5). Although different vaccines can significantly reduce hospitalization and mortality, breakthrough infections have been reported with all the vaccines used (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%